Communicating, Networking: Interacting: The International Year of Global Understanding - IYGU (2016)
We are all experiencing every day that globalization has brought and is bringing far-flung places and people into ever-closer contact. New kinds of supranational communities are emerging at an accelerating pace. At the same time, these trends do not efface the local. Globalization is also associated with a marked reaffirmation of cities and regions as distinctive forums of human action. All human actions remain in one way or the other regionally and locally contextualized. Global environmental change research has produced unambiguous scientific insights into earth system processes, yet these are only insufficiently translated into effective policies. In order to improve the science-policy cooperation, we need to deepen our knowledge of sociocultural contexts, to improve social and cultural acceptance of scientific knowledge, and to reach culturally differentiated paths to global sustainability on the basis of encompassing bottom-up action. The acceleration of globalization is bringing about a new world order. This involves both the integration of natural-human ecosystems and the emergence of an integrated global socioeconomic reality. The IYGU acknowledges that societies and cultures determine the ways we live with and shape our natural environment. The International Year of Global Understanding addresses the ways we live in an increasingly globalized world and the transformation of nature from the perspective of global sustainability-the objective the IYGU wishes to achieve for the sake of future generations. Initiated by the International Geographical Union (IGU), the 2016 IYGU was jointly proclaimed by the three global umbrella organizations of the natural sciences (ICSU), social sciences (ISSC), and the humanities (CIPSH). The IYGU is an outreach project with an educational and science orientation whose bottom-up logic complements that of existing UN programs (particularly the UN's Post-2015 Development Agenda and Sustainable Development Goals) and international research programs. It aims to strengthen transdisciplinarity across the whole field of scientific, political, and everyday activities.